Ayurveda Upachara on Amavata (International Journal of Ayurveda and Pharma Research, 2024)
This study delves into the positive impact of a 15-day Snehapana treatment on a patient, revealing significant relief from pain, reduced joint stiffness, and overall improvement. The subsequent follow-up assessment demonstrates the complete elimination of pain, swelling, sensitivity, and hardness. The success underscores the pivotal role of addressing Agni impairment, Ama formation, and Vata dosha vitiation in effectively managing Amavata. The sequential approach, encompassing the transformation of Ama into Niramaavasta, coupled with Virechan and Snehana treatments, proved to be successful. Notably, Snehana emerged as a crucial element, playing a key role in eliminating Ama-related issues, calming Vata, and clearing impurities. These findings provide valuable insights into a comprehensive and successful strategy for Amavata management, emphasizing the importance of a tailored treatment plan targeting the root causes of the condition.